PENGABDIAN MASYARAKAT SOSIALISASI DAN EDUKASI PENANGANAN DISMINOREA PADA REMAJA PUTRI DI SMK SEHATI KARAWANG - Rosmiyanti, Yanti; Sugihartini, Nining; Hafid, Indah Fitria; Desrianti, Cindy (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
Dysmenorrhea is pain felt in the lower abdomen during menstruation. One of the menstrual disorders that cause physical discomfort is dysmenorrhea. Dysmenorrhea is menstrual pain felt in the lower abdomen and radiating to the pelvis that can interfere with daily activities. One of the activities that can be disrupted is learning activities. Indonesia has a prevalence of dysmenorrhea reaching 98.8%. Based on the results of interviews conducted with 8 female students of SMK Sehatu Karawang, it was found that 7 young women experienced dysmenorrhea. Of the 7 young women who experience dysmenorrhea, only 1 young woman treats dysmenorrhea and 6 young women do not do treatment when experiencing dysmenorrhea. Dysmenorrhea has an impact on physical, psychological, social and economic conditions. This community service activity aims to provide education on knowledge and handling of dysmenorrhea in adolescent girls at SMK Sehati Karawang. The results of this community service are known to increase knowledge and understanding of the handling of dysminorrea in adolescent girls at SMK Sehati Karawang